2021
DOI: 10.1002/jeab.689
|View full text |Cite
|
Sign up to set email alerts
|

Matching, induction, and covariance with mixed response‐contingent food and noncontingent food

Abstract: The multiscale molar view of behavior is based on three basic laws of behavior: the Law of Allocation, the Law of Induction, and the Law of Covariance. Experiments that mix response-contingent food with noncontingent food shed light on these three laws. Food, like other phylogenetically important events, induces various activities that compete in allocation. Quantitative accounts represent induction with power functions. These power functions define activities' competitive weights, and relative time allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(171 reference statements)
0
8
0
Order By: Relevance
“…This view is also broadly consistent with the numerous studies that have demonstrated that operant reinforcers appear to have effects that are similar to the effect of discriminative stimuli (Ingvarsson & Kahng, 2006), as well as the literature on autoshaping mentioned above (Brown & Jenkins, 1968;Williams & Williams, 1969). For the present purposes, recent basic research with pigeons and rats suggests that the concept of PIEs as inducers might provide an alternative account of some of the research findings on the effects of response-independent schedules that seem inconsistent with the traditional view of operant reinforcement (Baum 2021;Baum & Aparicio, 2020;Baum & Grace, 2020).…”
Section: Phylogenetically Important Eventsmentioning
confidence: 81%
“…This view is also broadly consistent with the numerous studies that have demonstrated that operant reinforcers appear to have effects that are similar to the effect of discriminative stimuli (Ingvarsson & Kahng, 2006), as well as the literature on autoshaping mentioned above (Brown & Jenkins, 1968;Williams & Williams, 1969). For the present purposes, recent basic research with pigeons and rats suggests that the concept of PIEs as inducers might provide an alternative account of some of the research findings on the effects of response-independent schedules that seem inconsistent with the traditional view of operant reinforcement (Baum 2021;Baum & Aparicio, 2020;Baum & Grace, 2020).…”
Section: Phylogenetically Important Eventsmentioning
confidence: 81%
“…6 and 8 and Table 3). In experiments with mixed contingent and noncontingent food, the more noncontingent food, the lower the response rate (Baum, 2021;Baum & Aparicio, 2020;Rachlin & Baum, 1972). The reduction in operant responding may be explained by competition with nonoperant activity induced by the noncontingent food.…”
Section: Discussionmentioning
confidence: 99%
“…The Law of Induction proved essential to explaining performance on VI schedules (Baum, 2015;Baum & Grace, 2020) and avoidance (Baum 2020). The Law of Covariance was tested by mixing noncontingent food with contingent food and proved to be essential for explaining the resulting reductions in response rate (Baum, 2021;Baum & Aparicio, 2020;Rachlin & Baum, 1972). In those earlier studies, however, the noncontingent food played the role of an alternative source of food competing with the operant activity, whereas in the present experiment covariance itself was manipulated by varying the temporal lag between the operant pecking and the resulting food.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations